A new stag beetle species of the genus Gnaphaloryx Burmeister from Java, western Indonesia (Coleoptera: Lucanidae). (3rd April 2023) - Yamamoto, Shûhei; Qodri, Agmal
ABSTRACT: Tropical Indonesia has a rich biota. The fauna of stag beetles (Lucanidae) is relatively well understood in Indonesia, with numerous endemic species, including on the island of Java. Gnaphaloryx (Lucaninae: Dorcini) is a small genus of stag beetles mainly distributed in the Oriental Region. A new lucanid species, Gnaphaloryx rectus Yamamoto sp. nov ., is described from West Java, western Indonesia. This new species can be easily distinguished from the known Gnaphaloryx in the large males as it possesses symmetrical and rather linear mandibles, very weakly developed cephalic horn, weakly produced canthi, and narrower 2 nd and 3 rd costae on the elytra in comparison with the 1 st one. We provide a checklist of all species and subspecies of the genus with their known distributions. http://www.zoobank.org/urn:lsid:zoobank.org:pub:738C1CA7-8D54-46C4-90D6-97087356528F http://www.zoobank.org/urn:lsid:zoobank.org:act:211DA3A1-A08C-4291-BDC7-BAB3F69034C5